1-(3,4-Dichlorobenzyl)-3-methylquinolin-1-ium 7,7,8,8-tetracyanoquinodimethanide - Liu, Guang-Xiang (International Union of Crystallography, 2010)
In the title salt, C(17)H(14)Cl(2)N(+)·C(12)H(4)N(4) (−), cations and anions stack along the a axis into segregated columns by π–π stacking interactions, with alternating centroid–centroid separations of 3.5957 (7) and 3.7525 (7) Å for the cation column and 3.4252 (6) and 4.1578 (7) Å for the anion column. In the cation, the dihedral angle between the benzene ring and the quinoline ring system is 76.35 (4)°. The crystal packing is stabilized by intercolumnar C—H⋯N hydrogen bonds.